Diseño de estampados tomando como referencia las festividades del Corpus Christi del cantón Pujilí para público juvenil - Cajamarca Jácome, Fausto Efraín (2018)
Prints in clothing produced with reference in different cultures can have various functions some of them are underlined: Being a language that communicates a concise message about culture; evidence traces of beliefs and ideologies of people; fulfilling the function of prolonging the cultural style and traditions; displaying hierarchical brands of a community; symbolizing ethnic epistemologies enriched with history and fashion; and from the artistic point of view, expressing creativity, beauty and richness of graphic designs and materials. This research aims to motivate the culture in the field of fashion design, specifically in Graphic Design for prints; reflecting the festivity and tradition of Corpus Christi, which has endured throughout history, and which needs an adoption of new advertising strategies for its popular enrichment. The prints based on the dancer, one of the most representative figures of this festival, is what this work proposes when designing original graphics of this cultural festival for the application of the technique of stamping garments in order to strengthen the identity cultural activity in the young people of Pujilí canton; because the vast majority of youth use this type of fashion to go to different events and at the same time enhance the youthful novelty using them so that all people can appreciate them. The development of the research process applies the qualitative method, obtaining data of material preferences, colors, and so on; for the elaboration of the final product; It is based on specific objectives which are: To illustrate original graphics taking as a reference the parts of the dancer's attire, with the technique of printing on clothing, publicizing the cultural wealth of Pujilí and present a visual proposal. The cultural characteristics can be seen in each of the sketches in reference to the Dancer of the Corpus Christi festival, thus obtaining a pattern design model that helps promote, and rescue the cultural elements of the country with innovative sketches for the clients.